Developing social competence of religious college lecturers: Challenges and solutions - Sukri, Urbanus (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Lecturers' social competence is one of the most crucial aspects in efforts to improve the quality of education in higher education, especially in the environment of Religious Higher Education, where in addition to being required to have superior and in- depth academic abilities, lecturers must also be able to develop adequate social competence in order to establish effective and harmonious interactions with students, fellow colleagues, and the wider community; in this article, various challenges faced by lecturers in Religious Higher Education in the process of developing social competence are discussed in depth, as well as solutions that can be applied to overcome the obstacles that arise in order to improve the quality of their social competence; this study uses a qualitative approach that allows detailed identification of internal and external factors that influence the development of lecturers' social competence, while providing practical recommendations that are expected to be a reference in supporting the development of sustainable social competence in religious higher education. The results of this study indicate that the development of social competence of lecturers in religious universities faces various significant challenges such as the lack of specific training in social skills, differences in values and cultures that affect interactions between lecturers and students and colleagues, and high academic loads that limit the time and energy of lecturers to develop social aspects. Therefore, strategic solutions that need to be implemented include organizing training and workshops that focus on developing communication skills, conflict management, and leadership.